Research on student portal usage and its issues: a case study on Saudi Arabia universities, academic perspective - Suliman T Alatawi, Salem; Syed Abdullah, Norris; Miskon, Suraya (International Journal of Engineering and Technology, 2020)
With the rapid development of information and communication technologies (ICTs), having a website is inevitable for the organizations. Ministry of Saudi Arabia has adopted a policy to use ICT to universities to improve their university portals and services that they offer. Although having good ICT infrastructure in the Saudi Arabian universities, the usage of university portal still low. This paper aims to identify the current situation of studentâ€™s portal usage and its content issues that face student in Saudi Arabia universities, and how to solve these issues to produce good quality of portal content that can encourage the students to use the student portal. An online survey questionnaire was collected from 40 academic staff from various universities in Saudi Arabia, and reviewed a numbers of papers. The findings reveal that there is a lack of studentâ€™s portals contents, awareness of using ICT, and training and guidance. By enhancing quality of content that will increase the student satisfaction to use the portal, and that will help the university to produce good portal to their students.Â Â Â